Human 3D brain organoids: steering the demolecularization of brain and neurological diseases - Yogita K. Adlakha (Cell Death Discovery, 2023)
Abstract Understanding of human brain development, dysfunction and neurological diseases has remained limited and challenging due to inability to recapitulate human brain-specific features in animal models. Though the anatomy and physiology of the human brain has been understood in a remarkable way using post-mortem, pathological samples of human and animal models, however, modeling of human brain development and neurological diseases remains a challenge owing to distinct complexity of human brain. In this perspective, three-dimensional (3D) brain organoids have shown a beam of light. Tremendous growth in stem cell technologies has permitted the differentiation of pluripotent stem cells under 3D culture conditions into brain organoids, which recapitulate the unique features of human brain in many ways and also offer the detailed investigation of brain development, dysfunction and neurological diseases. Their translational value has also emerged and will benefit the society once the protocols for the upscaling of brain organoids are in place. Here, we summarize new advancements in methods for generation of more complex brain organoids including vascularized and mixed lineage tissue from PSCs. How synthetic biomaterials and microfluidic technology is boosting brain organoid development, has also been highlighted. We discuss the applications of brain organoids in studying preterm birth associated brain dysfunction; viral infections mediated neuroinflammation, neurodevelopmental and neurodegenerative diseases. We also highlight the translational value of brain organoids and current challenges that the field is experiencing.